2013
DOI: 10.1111/efp.12055
|View full text |Cite
|
Sign up to set email alerts
|

Fungi in foliage and shoots of Fraxinus excelsior in eastern Ukraine: a first report on Hymenoscyphus pseudoalbidus

Abstract: Summary In eastern Ukraine, the first symptoms of dieback on common ash (Fraxinus excelsior) were observed in 2010, as sparse flushing of leaves, bark necrosis and wood discoloration of shoots. The aim of this study was to assess possible causal agents of the damage by studying fungal communities in both symptomatic and healthy‐looking shoots, and leaf petioles. Field sampling was carried out in 2010 in Kharkiv and Sumy regions in eastern Ukraine and included 68 segments of symptomatic shoots, 68 segments of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 17 publications
4
48
0
6
Order By: Relevance
“…In Sweden, A. alternata was very frequent in both symptomless, healthy-looking shoots and in shoots with initial and advanced necroses (Bakys et al 2009a). In the Ukraine, A. alternata occurred in symptomatic shoots at a frequency more than twice that in the present study, but was absent from symptomless, healthy-looking shoots (Davydenko et al 2013). Artificial inoculation of 1-yearold F. excelsior seedlings showed that A. alternata only occasionally participates in the formation of stem necrosis (Bakys et al 2009a).…”
Section: Fungal Diversitysupporting
confidence: 42%
See 1 more Smart Citation
“…In Sweden, A. alternata was very frequent in both symptomless, healthy-looking shoots and in shoots with initial and advanced necroses (Bakys et al 2009a). In the Ukraine, A. alternata occurred in symptomatic shoots at a frequency more than twice that in the present study, but was absent from symptomless, healthy-looking shoots (Davydenko et al 2013). Artificial inoculation of 1-yearold F. excelsior seedlings showed that A. alternata only occasionally participates in the formation of stem necrosis (Bakys et al 2009a).…”
Section: Fungal Diversitysupporting
confidence: 42%
“…Similar results were reported from Sweden (Bakys et al 2009a, b). Most species that occurred commonly in this study have been found on stems and twigs of F. excelsior in various habitats (Butin and Kowalski 1986;Griffith and Boddy 1988, 1991Lygis et al 2005;Bakys et al 2009a;Chen 2012;Davydenko et al 2013).…”
Section: Fungal Diversitymentioning
confidence: 86%
“…doi: 10.17221/89/2014-PPS requirements of the fungus on the leaves, twigs, and branches of ash trees. Davydenko et al (2013) do not exclude that already in eastern Ukraine namely the continental climate might create less favourable conditions for the fungus. In our opinion it reduces even more the probability of the arrival of H. fraxineus in Europe alongside that "Krüssmann's ash belt".…”
Section: Resultsmentioning
confidence: 86%
“…Also, the range of H. fraxineus may enfold only the eastern part of the ranges of its hosts, where by today this fungus has been recorded (see Figure 24 in Baral & Bemmann 2014). Conversely, in Europe the still easternmost point of occurrence of H. fraxineus was established in eastern Ukraine (Davydenko et al 2013).…”
Section: Methodsmentioning
confidence: 98%
“…На основі досліджень висунуто ряд можливих збудників -гриби [13,10,6], бактерії [1,3,9], нематоди [5,8,11], мікоплазми [7,11,4], представники шкодочинної ентомофауни [4], а також вплив кліматичних [12] та ґрунтово-гідро логічних показників, проте єдиного консенсусу наразі не досягнуто. Між тим, у ясеневих насадженнях продовжують відбуватися патологічні зміни із листям, на сінням, деревиною, порушуються фотосинтезуючі та транспіраційні властивості, відбувається зниження технічної якості деревини і як наслідок -руйнування цілісності лісового біоценозу.…”
unclassified